Human-computer interaction -- INTERACT 2017 : 16th IFIP TC 13 International Conference, Mumbai, India, September 25-29, 2017, Proceedings.: 16th IFIP TC 13 International Conference, Mumbai, India, September 25-29, 2017, Proceedings. Part II (2017) - Unknown
No abstract available